Some legal problems of the criminal liability of legal persons abroad. (Journal of actual problems of jurisprudence, 2016)
In this article the problem of the criminal liability of legal persons, which may be considered as subjects of crime, criminal law for this problem is not new and quite debatable. It is one of the most complex and controversial issues, both foreign and domestic criminal law. In the history of the national criminal legislation known some cases of criminal liability of legal entities, which can be attributed to the examples of collective responsibility.
Keywords: criminal responsibility; legal person; law; crime